KAJIAN HUKUM DUALISME KEWENANGAN DALAM PENEGAKAN HUKUM TINDAK PIDANA PERIKANAN SETELAH DITETAPKAN- NYA UNDANG-UNDANG NOMOR 45 TAHUN 2009TENTANG PERIKANAN - Abdi Afriando; Zulfikar Jayakusuma; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The existence of Indonesia as one of the largest archipelagic countries in the world is a gift from God Almighty who created and is also the owner of the universe. On the third issue requires the establishment of fisheries courts throughout the territory of the Republic of Indonesia fisheries management. In this case the implementation of law enforcement in the fisheries sector becomes very important and strategic in order to support fisheries development. The spirit of the formation of this special justice is also based on the spirit to overcome the crisis of